BOBOT PENGARUH TIPE KEPRIBADIAN DAN PERSEPSI POLA ASUH TERHADAP KEJADIAN SKIZOFRENIA PADA PENDERITA RAWAT JALAN DI POLIKLINIK PSIKIATRI RSUP DR. SARDJITO DAERAH ISTIMEWA YOGYAKARTA - , SARI DEWI APRIYANTI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Etiology of schizophrenia interrelated to interaction developmental factors including individual, family, socio-economic, and culture. Personality types and parenting styles perception interrelated one another and affect schizophrenia event. Objectivity of this study to analyze personality types and parenting styles perception affect schizophrenia event compare with another developmental factors are like genetic, age, gender, education, occupation, marital-status, religiosity, physical stressors including infections disease and head injury, life styles including smoking, drugs and alcohol abuse, monthly income, and ethnic group. The expectation of this study can useful for community and healthy professional especially psychiatrists, patient, and caregiver for treatment. The type of this study is observational with case control analytic design. The subject is schizophrenia and non-schizophrenia on out-patient with caregiver in Psychiatry polyclinic of Dr. Sardjito Daerah Istimewa Yogyakarta by quota sampling. Extrovert and introvert personality is value by Extrovert-Introvert Personality Types Questioner. Traits of schizoid-schizotypal personality is value by Premorbid Schizoid-Schizotypal Traits (PSST). Parenting styles perception is value by Children Perception to Parenting Styles. Hypothesis tests use chi-square and multiple regression. The result of this study is find personality type only gives significant affect schizophrenia event (p < 0,05